Dynamic metabolic imaging of hyperpolarized [2‐13C]pyruvate using spiral chemical shift imaging with alternating spectral band excitation. Issue 6 (22nd July 2013) - Josan, Sonal; Hurd, Ralph; Park, Jae Mo; Yen, Yi‐Fen; Watkins, Ron; Pfefferbaum, Adolf; Spielman, Daniel; Mayer, Dirk
<x xml:space="preserve">Abstract</x> Purpose In contrast to [1‐13C]pyruvate, hyperpolarized [2‐13C]pyruvate permits the ability to follow the 13C label beyond flux through pyruvate dehydrogenase complex and investigate the incorporation of acetyl‐coenzyme A into different metabolic pathways. However, chemical shift imaging (CSI) with [2‐13C]pyruvate is challenging owing to the large spectral dispersion of the resonances, which also leads to severe chemical shift displacement artifacts for slice‐selective acquisitions. Methods This study introduces a sequence for three‐dimensional CSI of [2‐13C]pyruvate using spectrally selective excitation of limited frequency bands containing a subset of metabolites. Dynamic CSI data were acquired alternately from multiple frequency bands in phantoms for sequence testing and in vivo in rat heart. Results Phantom experiments verified the radiofrequency pulse design and demonstrated that the signal behavior of each group of resonances was unaffected by excitation of the other frequency bands. Dynamic three‐dimensional 13C CSI data demonstrated the sequence capability to image pyruvate, lactate, acetylcarnitine, glutamate, and acetoacetate, enabling the analysis of organ‐specific spectra and metabolite time courses. Conclusions The presented method allows CSI of widely separated resonances without chemical shift displacement artifact, acquiring multiple frequency bands alternately to obtain dynamic time‐course information. This approach enables robust imaging of downstream metabolic products of acetyl‐coenzyme A with hyperpolarized [2‐13C]pyruvate. Magn Reson Med 71:2051–2058, 2014. © 2013 Wiley Periodicals, Inc.